Uji Daya Hambat Ekstrak Metanol Kulit Bawang Merah (Allium cepa L.) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Pigdayanti Pigdayanti; Tutik Tutik; Selvi Marcellia (Jurnal Ilmiah Wahana Pendidikan, 2023)
Shallot peel (Allium cepa L.) is often considered as waste that is not useful by the community. This study aims to determine the shallot peel extract contains antibacterial against Staphylococcus aureus bacteria using the reflux method. The methods used in this study were sample collection, sample processing, extracting shallot skin samples, alcohol-free test, phytochemical screening, and antibacterial test using the disc method. The extraction method used, namely: Reflux method. This method is an extraction method by heating. the extraction yield obtained from the yield by the reflux method is 4.5%. Positive alcohol-free test results do not contain alcohol in the sample. The results of phytochemical screening of shallot peel extract showed the presence of alkaloids, flavonoids, saponins and phenolics. The results of inhibition test at a concentration of 5000ppm and 10000ppm obtained an average of 2.07 mm and 2,8 mm for each concentration. This research can be concluded that shallot peel extract (Allium cepa L.) has an inhibitory effect on the growth of Staphylococcus aureus bacteria with a weak category.